2013
DOI: 10.1016/j.actbio.2013.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Accurate characterization of pure silicon-substituted hydroxyapatite powders synthesized by a new precipitation route

Abstract: -Pottuz, et al.. Accurate characterization of pure silicon-substituted hydroxyapatite powders synthesized by a new precipitation route. Acta Materialia, Elsevier, 2013, 9 (6)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
77
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 110 publications
10
77
0
5
Order By: Relevance
“…La principale difficulté vient des précurseurs de silicium peu ou pas solubles qui conduisentà la précipitation de composés biphasés [4]. Desétapes préliminaires de solubilisation du silicium sous forme d'anion silicate en milieu aqueux semblent nécessairesà son incorporation directe dans l'apatite durant la précipitation [6].…”
Section: Apatites Carbonatées Ou Silicatéesunclassified
See 1 more Smart Citation
“…La principale difficulté vient des précurseurs de silicium peu ou pas solubles qui conduisentà la précipitation de composés biphasés [4]. Desétapes préliminaires de solubilisation du silicium sous forme d'anion silicate en milieu aqueux semblent nécessairesà son incorporation directe dans l'apatite durant la précipitation [6].…”
Section: Apatites Carbonatées Ou Silicatéesunclassified
“…Il apparait difficile de densifier totalement des apatites silicatées contenant plus de 0,5 mole de silicium par frittage naturel. Des travaux récents ont montré que la présence de vapeur d'eau dans l'atmosphère semble jouer ici aussi un rôle en augmentant la stabilité thermique de ces apatites [6].…”
Section: Apatites Silicatéesunclassified
“…HA and Si 0.5 HA powders were prepared according to the protocol described in detail elsewhere [9]. Reagents ratio used to prepare the Si 0.5 HA powders were calculated according to the formula Ca 10 (PO 4 ) 5.5 (SiO 4 ) 0.5 (OH) 1.5 and a constant molar ratio Ca/(P+Si) equals to 10/6.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, ionic substitution may be beneficial because can hinder aggregation, may increase loading efficiency as a consequence of a higher charge density, and may enhance dissolution of the endocytosed particles [106]. Silicon substitution of HAp has also been explored for non-viral gene delivery because great changes of properties (e.g., morphology, cell parameters, surface properties, crystallinity and kinetics of dissolution) have been reported [118][119][120]. Shekhar et al [106] demonstrated that the structure of HAp could be retained up to a 18.6 mol % of substitution of phosphates by silicates but an amorphous phase (i.e., for silicate contents between 16.6 and 33.3 mol %) and even new hydrated calcium silicate phases were formed at higher degrees of substitution.…”
Section: Hydroxyapatite As Non-viral Gene Delivery Systemmentioning
confidence: 99%
“…In fact, ionic substitution may be beneficial because can hinder aggregation, may increase loading efficiency as a consequence of a higher charge density, and may enhance dissolution of the endocytosed particles [106]. Silicon substitution of HAp has also been explored for non-viral gene delivery because great changes of properties (e.g., morphology, cell parameters, surface properties, crystallinity and kinetics of dissolution) have been reported [118][119][120].…”
Section: Hydroxyapatite As Non-viral Gene Delivery Systemmentioning
confidence: 99%